2018
DOI: 10.1002/phar.2193
|View full text |Cite|
|
Sign up to set email alerts
|

Reappraisal of Contemporary Pharmacokinetic and Pharmacodynamic Principles for Informing Aminoglycoside Dosing

Abstract: Therapeutic drug management is regularly performed for aminoglycosides in an effort to maximize their effectiveness and safety. The ratio of maximum plasma drug concentration to minimum inhibitory concentration (Cmax/MIC) has long been regarded as the primary pharmacokinetic/pharmacodynamic (PK/PD) index of clinical efficacy for aminoglycosides due to their concentration‐dependent killing. In this review, however, we discuss why the area under the plasma concentration–time curve (AUC)/MIC ratio may be a more r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
72
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 77 publications
(74 citation statements)
references
References 44 publications
(106 reference statements)
1
72
0
1
Order By: Relevance
“…We did not consider AUC as a predictor of nephrotoxicity. While several studies reported a relationship between aminoglycoside AUC and renal toxicity (5,7,27,28), no clear AUC target has been defined for once-daily amikacin. Further research is necessary about this question.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We did not consider AUC as a predictor of nephrotoxicity. While several studies reported a relationship between aminoglycoside AUC and renal toxicity (5,7,27,28), no clear AUC target has been defined for once-daily amikacin. Further research is necessary about this question.…”
Section: Discussionmentioning
confidence: 99%
“…Studied efficacy targets were C max /MIC of Ն8 and AUC 0 -24 /MIC of Ն75 (3,4). We considered three putative MIC values for probabilistic therapy: 8 mg/liter (the epidemiological cutoff for susceptible Enterobacteriaceae from EUCAST), 4 mg/liter (the Enterobacteriaceae MIC breakpoint from USCAST), and a lower value of 2 mg/liter (5,49). C max was calculated as the concentration obtained 1 h after the start of the 30-min infusion (3).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Increasing aminoglycoside PK/PD exposures has been a recommended approach for severe lifethreatening infections. 5 A target-free AUC 0-24 hr -tominimum inhibitory concentration (MIC) above 110 has been proposed for lung infections. 17 In CF, prolonged aminoglycoside exposure may contribute to higher aminoglycoside MICs and reduced PK/PD attainment.…”
Section: Discussionmentioning
confidence: 99%
“…In Bland et al . the treatment protocol in section “Support for the Cmax/MIC Ratio as a PK/PD Index” was published with error.…”
mentioning
confidence: 99%